Triboelectric Charging Properties of the Functional Groups of Common Pharmaceutical Materials Using Density Functional Theory Calculations - James R. Middleton; Mojtaba Ghadiri; Andrew J. Scott (MDPI AG, 2024)
Triboelectrification is a ubiquitous and poorly understood phenomenon in powder processing, particularly for pharmaceutical powders. Charged particles can adhere to vessel walls, causing sheeting; they can also cause agglomeration, threatening the stability of powder formulations, and in extreme cases electrostatic discharges, which present a serious fire and explosion hazard. Triboelectrification is highly sensitive to environmental and material conditions, which makes it very difficult to compare experimental results from different publications. In this work, density functional theory (DFT) is used to investigate the charge transfer characteristics of several functional groups of paracetamol in order to better understand the mechanisms of charging at the nanoscale and the influence of the environmental and material properties on charge transfer. This is achieved by studying the structure and electronic properties at the molecule-substrate interface. Using this molecule-substrate approach, the charging contributions of individual functional groups are explored by examining the Hirschfeld charges, the charge density difference between the molecule and substrate, the density of states, and the location of the frontier orbitals (HOMO and LUMO) of a paracetamol molecule. Charge density difference calculations indicate a significant transfer of charge from the molecule to the surface. Observable regions of electron density enrichment and depletion are evident around the electron-donating and -withdrawing groups, respectively. The density of states for the paracetamol molecule evolves as it approaches the surface, and the band gap disappears upon contact with the substrate. Hirshfeld charge analysis reveals asymmetry in the charge redistribution around the molecule, highlighting the varying charging tendencies of different atoms.